2019
DOI: 10.3389/fneur.2019.00898
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and the Development of a Personalized Medicine Approach in Spinal Muscular Atrophy

Abstract: Recent unprecedented advances in treatment for spinal muscular atrophy (SMA) enabled patients to access the first approved disease modifying therapy for the condition. There are however many uncertainties, regarding timing of treatment initiation, response to intervention, treatment effects and long-term outcomes, which are complicated by the evolving phenotypes seen in the post-treatment era for patients with SMA. Biomarkers of disease, with diagnostic, prognostic, predictive, and pharmacodynamic value are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 113 publications
(145 reference statements)
3
44
0
1
Order By: Relevance
“…This knowledge would help to identify prognostic factors, to avoid long-term exposure to expensive drugs with still unknown long-term drug-related adverse events. A variety of biomarkers is currently under investigation including epigenetic, genetic, proteomic, electrophysiological and imaging tools [ 83 ]. Neurofilaments (NFs) muscle-specific miRNAs (myomiRs) and CSF proteomic profile, although biomarkers are not yet validated, have recently drawn attention as promising tools in SMA.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge would help to identify prognostic factors, to avoid long-term exposure to expensive drugs with still unknown long-term drug-related adverse events. A variety of biomarkers is currently under investigation including epigenetic, genetic, proteomic, electrophysiological and imaging tools [ 83 ]. Neurofilaments (NFs) muscle-specific miRNAs (myomiRs) and CSF proteomic profile, although biomarkers are not yet validated, have recently drawn attention as promising tools in SMA.…”
Section: Discussionmentioning
confidence: 99%
“…The considerable heterogeneity and slow disease progression in adults with SMA has contributed to the paucity of research and lack of efficacy in the limited number of trials to date. Clinical trials which could address this issue require long durations and robust clinical outcome measures, drawing attention to the need for biomarkers which are sensitive to changes in disease progression and/or response to disease modifying agents [120]. Unlike studies in infants and children with SMA, in which circulating neurofilaments are emerging as potential measures to assess disease progression and response to nusinersen treatment [121], no studies in adults with SMA have yielded a robust, reliable measurement [86,88,[122][123][124][125][126].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from SMN2 copy numbers, a variety of other possible biomarkers are currently discussed and investigated [62]. Within the ENDEAR study population, symptomatic SMA type 1 patients showed higher levels of plasma phosphorylated neurofilament heavy chain (pNF-H) than healthy controls.…”
Section: Biomarkers In Smamentioning
confidence: 99%